O modelo instrucional 5e e o ensino de química: definições e estratégias - SOARES , Sanley Viegas (2022)
The Active Methodologies have, among others, the objective of developing the teaching learning process using real experiences, seeking to successfully solve challenges directly linked to the essential activities of society in different contexts. Challenges were plentiful in this period of global health crisis in which remote teaching started to be presented as an emergency solution for the continuity of the schooling process. This work was conducted before and during the initial critical days of the pandemic in a private school in São Luís (MA), during high school chemistry classes, having as a general objective to identify the applicability of Active Methodologies in Chemistry Teaching, specifically the 5E instructional model (Engage, Explore, Explain, Elaborate and Evaluate). To achieve this objective, applied and explanatory research was adopted, using as theoretical reference authors such as: Duran, Bock, Arroio, Tyler, Zabala, Moran and Fernandes. The 5E instructional method (Engage, Explore, Explain, Elaborate and Evaluate) was used in the hybrid and remote approaches for a more captivating process of teaching and learning. The data were collected through observation during the classes and through the application of questionnaires. The referential analysis was based on the works of Sasseron and Carvalho, and of Bardin, identifying, through content analysis, the indicators of scientific literacy in each of the 5E model stages. The results found the presence of scientific literacy indicators in all stages of the present instructional model in the hybrid and only remote formats, which highlights the importance and efficiency of the application of active teaching methods for the construction of knowledge, autonomy, and critical thinking.